THEORETICAL APPROACH ON THE NITROGEN POTENTIAL CONTRIBUTION FROM SUSTAINABLE NATURAL FERTILIZATION WITH CATTLE MANURE - Rodica CHETROIU; Diana Maria ILIE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to present a theoretical approach on the nitrogen potential contribution of the cattle manure for natural and sustainable soil fertilization, on different development regions of Romania, during 2017-2021. Calculations are based on statistical data provided by Ministry of Agriculture and Rural Development and National Institute of Statistics. Taking into account the maximum amount of nitrogen of 170 kg/ha that can be administered, the share of the nitrogen coverage potential from cattle manure was determined for each development region and for the different crops. The results showed that the amounts of nutrients from cattle manure could cover different shares for different crops, and for many of them, even 100%, like legumes, or potatoes, or vegetables, or orchards for fruit. The sustainable fertilization of the cattle manure represents a valuable argument for the importance of this species – bovine, in the present opinion exchanges.